Precision electroweak measurements on the Z resonance - Schael, S; Barate, R; Bruneliere, R; Buskulic, D; De Bonis, I; Decamp, D; Ghez, P; Goy, C; Jezequel, S; Lees, J; Lucotte, A; Martin, F; et al. (2006)
We report on the final electroweak measurements performed with data taken at the Z resonance by the experiments operating at the electron-positron colliders SLC and LEP. The data consist of 17 million Z decays accumulated by the ALEPH, DELPHI, L3 and OPAL experiments at LEP, and 600 thousand Z decays by the SLD experiment using a polarised beam at SLC. The measurements include cross-sections, forward-backward asymmetries and polarised asymmetries. The mass and width of the Z boson, mZ Z, and ΓZ, its couplings to fermions, for example the ρ parameter and the efffective electroweak mixing angle for leptons, are precisely measured: mZ = 91.1875 ± 0.0021 GeV, ΓZ = 2.4952 ± 0.0023 GeV, ρℓ = 1.0050 ± 0.0010, sin2 θefflept = 0.23153 ± 0.00016. The number of light neutrino species is determined to be 2.9840 ± 0.0082, in agreement with the three observed generations of fundamental fermions. The results are compared to the predictions of the Standard Model (SM). At the Z-pole, electroweak radiative corrections beyond the running of the QED and QCD coupling constants are observed with a significance of five standard deviations, and in agreement with the Standard Model. Of the many Z-pole measurements, the forward-backward asymmetry in b-quark production shows the largest difference with respect to its SM expectation, at the level of 2.8 standard deviations. Through radiative corrections evaluated in the framework of the Standard Model, the Z-pole data are also used to predict the mass of the top quark, mt = 173-10+13 GeV, and the mass of the W boson, mW = 80.363 ± 0.032 GeV. These indirect constraints are compared to the direct measurements, providing a stringent test of the SM. Using in addition the direct measurements of mt and mW, the mass of the as yet unobserved SM Higgs boson is predicted with a relative uncertainty of about 50% and found to be less than 285 GeV at 95% confidence level. © 2006 Elsevier B.V. All rights reserved.